Autophagy-enhancing strategies to promote intestinal viral resistance and mucosal barrier function in SARS-CoV-2 infection - Anusca G. Rader; Alexandra P.M. Cloherty; Kharishma S. Patel; Dima D.A. Almandawi; Jimena Perez-Vargas; Manon E. Wildenberg; Vanesa Muncan; Renée R.C.E. Schreurs; François Jean; Carla M.S. Ribeiro (Autophagy Reports)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of Coronavirus disease 19 (COVID-19), continues to circulate globally despite the widespread vaccination and therapeutics like Paxlovid, remdesivir, and molnupiravir. COVID-19 is associated with both respiratory and gastrointestinal manifestations, with persistent intestinal pathology contributing to the post-COVID-19 condition. We have previously demonstrated the antiviral activity of autophagy-blocking drugs, such as Berbamine dihydrochloride, against intestinal SARS-CoV-2 acquisition. In addition, the autophagy blockers restored the barrier function of infected intestinal epithelium. In this addendum, using human intestinal organoids, we present evidence for a protective role of intrinsic higher levels of autophagy flux in limiting intestinal SARS-CoV-2 infection. Pharmacological treatment with Akt inhibitor MK-2206 hydrochloride suppressed viral entry into the intestinal epithelium. This antiviral effect of MK-2206 was shown to be dependent on Synaptosomal-associated protein 29-dependent (SNAP-29)-mediated autophagy flux. Furthermore, extrinsically enhanced autophagy with MK-2206 also prevented SARS-CoV-2-induced intestinal barrier damage. Our findings thus underscore the intricate role of autophagy pathways in the dissemination and pathogenesis of intestinal SARS-CoV-2, highlighting the therapeutic potential of host-directed therapies targeting autophagy to intervene in COVID-19-associated sequelae and improve intestinal health.